A EXPORTAÇÃO DO TRABALHO ESCRAVO CONTEMPORÂNEO: internacionalização do Modelo Sucroenergético Brasileiro Para a África - Viviane Regina da Silva (Universidade Federal do Maranhão, 2014)
The goal of this essay was to expose to discussion the exportation problematic of the perverse model of slave labor through the Brazil’s International Cooperation with Africans countries in the sugarcane industry. The essay still emphasizes, that, considering the geopolitics conflicts resulting of petrol scarcity, the global climate changing and the growing demand for fuels in an ascendant global economy, these cooperations aim to stimulate the renewable energies production using ethanol based in sugarcane. It mentions the legal, historical and statistics bases that characterize the labor in this sector like a slave labor, with a new point of view, nevertheless much resident in the Brazilian’s agriculture. Looking up to list yet, many Brazilian Government acts looking for create cooperation in this area that shows up the crescent danger of exportation of the slave labor to the African continent, aggravated by the partnership seal of development.